Použití (mikro)ekonomické metodologie při tvorbě a interpretaci soukromého práva - Tomáš Richter (Charles University in Prague, Institute of Economic Studies (IES), 2008)
– The paper reviews (in Czech) the main qualitative tools applied by (micro)economic analysis and surveys the main literature on the topic. Economics is often being criticised by its opponents for the use of unrealistic assumptions. On the contrary, my claim is that if economics has anything to contribute to legal analysis, it is above all exactly these assumptions and their unrealism. Not in the sense in which assumptions help economic modelling but in the sense that by spelling out expressly what our world is not like, economics alerts the lawyer to imperfections and frictions that he or she all too often fails to reflect in his or her legal analysis. I call this up-shot of the assumptions used by microeconomics a reversed codification of the imperfections of our world and in the paper, I go over the bulk of the more important ones and try to show how the fact that the world is not as assumed by the various economic schools of thought might affect human behaviour and therefore the rules of law aimed at regulating that behaviour. I start the review with the rational maximisation assumption and then go over the many carve-outs from it. First, I discuss the limits of rationality and of human cognitive abilities and how they impact on contracts and legal rules. Secondly, I turn to what might go wrong when people act too rationally - i.e. when adverse selection and moral hazard are introduced. In this part, I deal with Jensen and Meckling's agency problems, with collective choice issues and with several game theoretical concepts that help predict the effects of self-interested human behaviour. I then explain how the Coase theorem might enlighten the legal mind not in its original expression but rather in its reversal, i.e. in the claim that in a world in which transaction costs are pervasive, rules of law may very well determine how rights will be allocated. In this context, I also mention externalities. In the third part, I introduce normative law and economics and its main tools, Pareto and Kaldor-Hicks efficiency. I briefly review the philosophical controversy about the normative use of economics in the law and explain my own provisional stance on the issue. I close the paper with several observations on how the methodology used by positive economics may assist the legislator, whether it follows paternalistic or liberal policies. I conclude by saying that while that methodology should not be expected to displace other frames of reference used by lawyers, without it, legal theory, in particular in the private law field, will be incomplete while the legislator and the judiciary may promulgate rules that will complicate rather than facilitate private ordering.
Keywords: B41; K00; 330; economic analysis of law; microeconomic methodology; assumptions used in microeconomics; Wirtschaftswissenschaft; Mikroökonomik; Rechtsökonomik; Privatrecht; Theorie